Dynamics of World Indices as a Reflection of the Development World Financial Market - Lyashenko, V.; Bril, M.; Shapran, O. (IJAAFMR, 2021)
Economic dynamics are closely interconnected with various segments of economic relations. A special role among such relationships is formed in the financial markets. This is due to the ability to attract the necessary financial resources or redistribute financial resources between various business entities. This can be achieved with the help of various groups of securities. Ea ch such group of securities is also characterized by some stock index. This index reflects the dynamics of securities prices. Consequently, the dynamics of stock indices is a reflection of the dynamics of the development of the financial market. To study the dynamics of stock indices, we use the ideology of wavelets. We have chosen wavelet coherence among the tools of the wavelet ideology. Wavelet coherence allows you to study the mutual dynamics of stock indices and draw the necessary conclusions. The paper examines the dynamics of the main world stock indices. The estimates of the wavelet coherence for the mutual dynamics of stock indices are shown. All results are based on real data. The conclusion is made about the expediency of using wavelet coherence for assessing the mutual dynamics of stock indices and assessing the development of the financial market.
Keywords: time series; wavelet coherence